Representasi Solastalgia dan Distress Lingkungan dalam Film Dokumenter Pesta Babi: Analisis Konten Kualitatif Berbasis Ekopsikologi - Laely Nur Azizah; Nur Azizah (Journal of Society Counseling, 2026)
Documentary films offer a distinctive window into the psychological suffering that communities endure when their home environments undergo severe and sustained degradation. The documentary Pesta Babi captures how rural communities bear the weight of environmental harm caused by large-scale industrial pig farming. This study analyzes the manifestation of solastalgia and environmental distress as portrayed in the film, employing qualitative content analysis grounded in ecopsychology theory and Albrecht's solastalgia framework. Data were gathered through close observation of visual narratives, dialogue, affective expressions, and symbolic elements, triangulated with secondary sources. Three dominant dimensions of solastalgia emerged from the analysis: first, loss of place attachment, marked by landscape transformation and the erosion of the symbolic meaning communities had woven into their surroundings; second, chronic ecological distress, expressed through persistent anxiety and collective psychological exhaustion; and third, erosion of communal identity, tied to the disappearance of natural resources as both livelihood and anchor of selfhood. The study affirms that documentary film is not merely an advocacy instrument but also a documentation space for collective psychological suffering that warrants serious attention from counseling practitioners. These findings contribute to the development of contextual, community-based, and ecologically grounded eco-counseling within Islamic guidance and counseling in Indonesia.